2014
DOI: 10.1021/ef5005418
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Studies of the Sequential Dewatering/Dry Separation of Chinese Lignite in a Vibration Fluidized-Bed Dryer: Effect of Physical Parameters and Operation Conditions

Abstract: The combined dewatering process and dry separation in a vibration fluidized-bed dryer was developed to upgrade Chinese lignite in terms of moisture and ash for effective utilization in power plants. The influence of operational parameters (fluidizing gas velocity, vibration strength, bed height, and drying temperature) and lignite properties (particle size and moisture content) on the drying or separation characteristics of −6−1 mm lignite was examined in a laboratory-scale vibration fluidizedbed dryer. Both o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…8. Zhao et al [66] found that the fluidizing gas velocity, vibration strength, bed height and drying temperature had significant effect on the drying and separation performance of 6-3 mm and 3-1 mm size fractions lignite. Meanwhile, the drying and separation performance is significantly affected by lignite properties, such as lignite particles and surface moisture content.…”
Section: Dry Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8. Zhao et al [66] found that the fluidizing gas velocity, vibration strength, bed height and drying temperature had significant effect on the drying and separation performance of 6-3 mm and 3-1 mm size fractions lignite. Meanwhile, the drying and separation performance is significantly affected by lignite properties, such as lignite particles and surface moisture content.…”
Section: Dry Methodsmentioning
confidence: 99%
“…8. Schematic representation of a sequential drying and separation process in a vibro-fluidized-bed dryer [66]. clean coal with 66.41% total sulfur, 97.71% inorganic sulfur and 79.52% ash content.…”
Section: Chemical Leachingmentioning
confidence: 99%
“…For the size of 1-3 mm, the dry beneficiation method using a special vibration fluidized bed can be found in our previous studies [14,36]. After fluidization for a certain time, this bed was divided into five layers in the axial direction and the ash content of each layer was measured.…”
Section: Lignite Propertiesmentioning
confidence: 99%
“…Numerous coal cleaning technologies associated to de-watering [6][7][8][9][10] and de-ashing [11][12][13][14] processes have been proposed to sustainably utilize these lignites. However, most of them were not yet widely practiced by the power industry considering the high consumption of energy required during cleaning processes.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Therefore, the development of al ignite dehydration technology would assist in increasingi ts comprehensive utilization and save production costs.T he current commonly used methodi sd rying, such as by using non-evaporation dewatering, hot air, pyrogenation, and hot pressing. [8] However, the high volatile component content in lignite easily causes fires and explosions.M oreover, its drying efficiencyi sl ow and the product moisturei s usuallyu nstable because of the high lignite moisture content. [9] Moisture control of fine lignite has therefore become ar esearche mphasis andh otspoti nt he coal preparation industry and is am ajor challenge in the coal industry in terms of time,l abor, and cost savings.I ti sa lso one of the bottlenecks that limits the development of clean coal technology.…”
Section: Introductionmentioning
confidence: 99%